Representasi Kekerasan Pada Anak Dalam Film Benalu Karya Sidiq Aryadi (Analisis Semiotika Roland Barthes) - Wahyuningsih, Linda (CV. Lenggogeni Data Publishing, 2024)
This research aims to determine the meaning of the denotation and connotation of forms of verbal abuse against children as well as the meaning of the myth of verbal abuse against children in the film Benalu by Sidiq Aryadi. The data analysis technique used is semiotic analysis, namely, Roland Barthes' Semiotic Analysis, to reveal the meaning of connotative, denotative signs, and myt. Verbal abuse is